Transcriptome of rhesus macaque (Macaca mulatta) exposed to total-body irradiation - Yaoxiang Li (Nature Portfolio, 2021)
Abstract The field of biodosimetry has seen a paradigm shift towards an increased use of molecular phenotyping technologies including omics and miRNA, in addition to conventional cytogenetic techniques. Here, we have used a nonhuman primate (NHP) model to study the impact of gamma-irradiation on alterations in blood-based gene expression. With a goal to delineate radiation induced changes in gene expression, we followed eight NHPs for 60 days after exposure to 6.5 Gy gamma-radiation for survival outcomes. Analysis of differential gene expression in response to radiation exposure yielded 26,944 dysregulated genes that were not significantly impacted by sex. Further analysis showed an increased association of several pathways including IL-3 signaling, ephrin receptor signaling, ErbB signaling, nitric oxide signaling in the cardiovascular system, Wnt/β-catenin signaling, and inflammasome pathway, which were associated with positive survival outcomes in NHPs after acute exposure to radiation. This study provides novel insights into major pathways and networks involved in radiation-induced injuries that may identify biomarkers for radiation injury.